Machining properties of 25 and 50 year old treated oil palm lumber / Muhamad Hafiz Md Saad and Ahmad Fauzi Awang@Othman - Md Saad, Muhamad Hafiz; Awang @Othman, Ahmad Fauzi (2015)
Wood had become one the most important material in furniture industry. Nowadays, with the decreasing supply of good timber for furniture industry and the increasing cost of wood materials, oil palm lumber can become one of the replacement materials resources to support the demand in industry. This research is to determine the machining properties of oil palm lumber with different age which are 25 and 50 year old and different layer of oil palm lumber which are outer, middle and inner. Several types of testing have been used on this research which are planning, sanding, boring, mortising, moulding and turning. Different results have been recorded after those testing are applied to the samples because of the several factors that influence their machining properties. 50 year old oil palm lumber give better performances than 25 yea, old oil palm lumber and outer layer give good machining properties than middle and inner layer. However, 25 year old oil palm lumber also can be used in machining process if better machining technique is adopted in further study.